Arch of the Rising Sun (Pacific Novelty Co.)
On verso: In the foreground is part of the Court of Flowers and in the distance first the Fountains of The Rising and Setting Sun and next the Arch of the Setting Sun. These two triumphal arches are crowned by colossal groups of statuary representing "Nations of the East" and "Nations of the West" here brought face to face in the Court of the Universe.